COGNITIVE-PRAGMATIC ANALYSIS OF EUPHEMISMS IN ENGLISH AND UZBEK LINGUOCULTURE - Gulnora Mavlonova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Euphemisms are a significant linguistic occurrence that illustrates the interplay of language, culture, and cognition. They are frequently employed in communication to soften negative connotations, steer clear of sensitive subjects, and uphold social courtesy. This study examines the cognitive-pragmatic dimensions of euphemisms within English and Uzbek linguistic cultures. The objective is to explore the conceptual processes behind euphemistic phrases and to determine their communicative roles across various cultural settings. This research utilizes qualitative and comparative approaches to examine euphemistic terms gathered from dictionaries, literary works, and media. The study reveals that euphemisms in both languages serve comparable pragmatic purposes, including politeness, softening impact, and conveying messages indirectly. Nevertheless, cultural standards affect how euphemistic expressions are conceived and how often they are used. The outcomes suggest that euphemisms represent both universal cognitive processes and communication strategies specific to particular cultures.